DETERMINATION BIO-EFFICACY OF INSECTICIDES AGAINST LITCHI STINK BUG, TESSARATOMA JAVANICA (THUNBERG) (HEMIPTERA: TESSARATOMIDAE): AN EMERGING MAJOR PEST OF LITCHI, LITCHI CHINENSIS SONN - JAIPAL SINGH CHOUDHARY; MOANARO; NAIYAR NAAZ; MD. IDRIS (The Bioscan, 2015)
Keeping in view of damage potentiality of litchi stink bug, dose mortality response of seventeen numbers of insecticides was evaluated to find out efficacious alternative for management of litchi stink bug menace. Among the evaluated insecticides viz., Dichlorvos 76 EC showed maximum mortality (100%) followed by 86.67 per cent mortality to 1st instar nymphs by Acephate 75 SP, quinalphos 25 EC and thiodicarb 75 WP within 24 hours at field dosage of insecticides. The data on relative toxicity against 1st instar nymphs revealed that chlorantraniliprole, thiacloprid, thiodicarb and spinosad were 36.83, 27.62, 22.10 and 10.04 times more toxic with reference to novaluron, respectively. The order of toxicity based on LC50 values, chlorantraniliprole, thiacloprid, thiodicarb and acephate were found efficacious. Therefore, it is suggesting that field mortality of younger stages of stink bug nymphs could be enhanced by increasing concentration of chlorantraniliprole, thiacloprid, thiodicarb and spinosad which can be incorporate into management modules of stink bugs.